Low energy synthesis of crystalline cellulose nanofibers from Pennisetum hohenackeri by planetary ball milling - Susithra Sureshkumar; Dhruvkumar Bharatbhai Patel; Swambabu Varanasi (Carbohydrate Polymer Technologies and Applications)
Cellulose nanofibers (CNFs), a new-age bio-based nanomaterial with excellent properties, have not yet been widely commercialized due to complex synthesis methodologies and high fibrillation energy consumption, leading to elevated production costs. Consequently, there is a critical need for a low-fibrillation energy, cost-effective, and easily scalable synthesis route for CNFs. Regardless of the fibrillation method, the biomass source plays a vital role in reducing the energy required for fibrillation. This study synergistically explored a novel biomass source with lower lignin and higher hemicellulose content, a suitable bleaching and delignification method that retains predominant hemicellulose while removing lignin and other extractives, and an efficient fibrillation route. Raw Pennisetum hohenackeri (fountain grass) was processed to produce a pulp with 20 % hemicellulose content, lower lignin content, and a carboxylate content of 0.42 mmol/g in the grass, allowing the production of CNFs with just 5 min of planetary ball milling, without any mechanical or chemical pre-treatments. The synthesized CNFs had an average diameter of 13 nm (±6 nm) and a crystallinity index of 76 %. The tensile strength of CNF films were comparable to values reported in the literature. The energy required for fibrillation was 2.95 kWh/kg, the lowest reported so far. This eco-friendly and energy-efficient fibrillation method offers a sustainable alternative for CNF production, promoting the use of renewable biomass resources.